Entrepreneurial intention of Indonesian migrant workers / Damar Aji Irawan, Abdul Qadir A Syakur and Hasan Maududi - Aji Irawan, Damar; A Syakur, Abdul Qadir; Maududi, Hasan (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
This research aims to find out the effect of psychological characteristics and entrepreneurship training towards entrepreneurial intention of Indonesian Migrant Workers. This study is a quantitative research, and non-probability purposive sampling was used to select participants. There are 68 respondents that met the sample criteria. To analyze the data, this research uses partial least square (PLS) technique. The results showed that psychological characteristics and entrepreneurship training have positive and significant effect towards entrepreneurial intention and the relationship between entrepreneurship training and entrepreneurial intention could not be moderated by psychological characteristics.